Male Chauvinism, Cultural Hybridity and Racism in the Society of Indian Sub-Continent : A Study of Bollywood's Film Pinjar Semiotically - Hamza, Hassan; Miaw Lee, Teo (Creative Saplings, 2022)
The words racism, cultural hegemony, and male chauvinism are frequently used in Indo-Pak literature and film. The Indian Subcontinent is known for having a male-dominated culture, a fusion of several ethnic and racial groups, and a society in that men dominate. The movie Pinjar, based on a novel, depicts various cultures, conventions, beliefs, and traditions from the time before and after the 1947 partition of the Indian subcontinent while showcasing numerous literary and critical facets. This research on the movie Pinjar focuses on racism, cultural hegemony, and male chauvinism. This particular video has used the semiotics framework—the study of signs, colors, and language—as the main framework to follow all the relevant elements.